KAKAWIN CALON ARANG KARYA NYOMAN ADIPUTRA DALAM KAJIAN INTERTEKSTUAL - Prabawa Redi, A. A. Ngr. Mukti (Humanis; Volume 7. No. 1. April 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Kakawin Calon Arang (KCA) is a kind of old Java poetry with ancient old Java language that are created in this century, therefore, this kakawin can be classified into kakawin minor, considering its emergence in Balinese tradition and culture. This kakawin was written in 18 sargah with 530 pada (verse) , KCA appears from literature tradition that has existing before in a form of prose of LOr 5387/5279 manuscript which shows that the KCA writer is able and dare todo a text transformation process from prose into poetry (kakawin) In order to gain a clear understanding of the writing process of KCA, two basic theories are underlying this minithesis in the analysis process, they are structural theory and intertext theory. The structural theory analysis are based on Teeuw’s theory, Dick Hartoko’s opinion which scop e the analysis on the formal structure analysis and composition structure, while the intertext analysis are based on Kristeva’s opinion. Based on the intertext analysis there is found that the writer of KCA were not fully using the LOr 5387/5279 manuscript to build the narative structure. Then, from the 18 sargah in the text, there are only three sargah: I, II, and XI which show strong interelationship between the LOr 5387/5279 manuscript and KCA. The other sargah: III, IV, V, VI, VII, VIII, IX, X, ,XII, XIII, XIV, XV, XVI, XVII, XVIII show that the writer of KCA has widen the intrinsict elements, which lessen the in the relationship story between the LOr 5387/5279 manuscript and the KCA, including the theme that in LOr 5387/5279 manuscript is about moksa,while in KCA is about panyupatan. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: Kakawin Calon Arang, old javanese language, intertertext, text transformation, moksa, panyupatan.